Evaluation of pulpal response of deciduous teeth after direct pulp capping with bioactive glass and mineral trioxide aggregate - Roza Haghgoo; Motahare Ahmadvand (Wolters Kluwer Medknow Publications, 2016)
Aim: The aim of this study was to evaluate the pulpal response of primary teeth after direct pulp capping (DPC) with two biocompatible materials namely mineral trioxide aggregate (MTA) and bioactive glass (BAG). Settings and Design: This study was a randomized clinical trial. Materials and Methods: A total of 22 healthy primary canine teeth scheduled for extraction for orthodontic reasons were selected. The teeth were divided into two groups of 11 and underwent DPC. The exposure sites were randomly capped with MTA or BAG in the two groups. After 2 months, the teeth were extracted and prepared for histopathologic evaluation. Statistical Analysis: The data were analyzed using Fisher's exact test. Results: In the BAG group, inflammation was seen in three patients; internal resorption and abscess were not seen at all. In the MTA group, inflammation was seen in one patient and internal resorption and abscess were not seen in any patient. Fisher's exact test showed no significant difference between the two groups (P > 0.05). Dentinal bridge formation was noted in five patients in the BAG group and six patients in the MTA group. No significant difference was observed between the BAG and MTA groups using Chi-square analysis (P = 0.67). Conclusion: Based on the results of this study, MTA and BAG can be used for DPC of primary teeth.